Stuart Woods' Deep water [large type] - Battles, Brett (Woods, Stuart. Stone Barrington novel, 2026)
"When Stone Barrington meets one of his clients, Trenton Sidney, for a sunset drink on Trenton's new yacht, the last thing he expects is to be a victim of a shipwreck. As one of the four survivors of the incident but with little memory of the sinking, Stone finds himself diving straight back into work. His first task? To reach out to the beneficiaries in Trenton's will. But when new evidence that points to foul play comes to light, Stone must probe the tragedy in more ways than one in order to uncover the identity of the perpetrator . . . before they find another lethal way to get themselves out of deep water."--